DAMPAK MERGER DAN AKUISISI PADA KINERJA KEUANGAN (STUDI KASUS SEKTOR PERBANKAN DI INDONESIA) - Rosalia Nansih Widhiastuti (Institut Teknologi dan Bisnis Swadharma, 2021)
The purpose of companies conducting mergers and acquisitions is to expect benefits for fellow companies. This advantage will occur if the merger and acquisition activities result in good synergy to improve company performance. The purpose of this study is to determine whether there are differences in financial performance and banking health conditions before and after mergers and acquisitions. This study uses the RGEC (Risk Profile, Good Corporate Governance, Earning, Capital) variable. The population in this study were all banks listed on the IDX for the period 2004-2018. The technique used in sampling is purposive sampling, in order to obtain a total of 6 banks in the study sample. The data analysis method used was the Paired Sample T-Test and the Wilxocon Signed Ranks Test. The results of the analysis show that there are significant differences in the ratio of NPL, ROA, NIM, and CAR between before and after the merger and acquisition